STUDY OF PHYTOTOXIC AND PHYTOPATHOGENIC PROPERTIES OF DRECHSLERA TRITICI-REPENTIS FUNGI - Tagimanova, D.S.; Khapilina, O.N.; Sozinova , L.F. (Eurasian Journal of Applied Biotechnology, 2013)
One of the main causes of losses in grain yield in Kazakhstan is the rapid development of fungal diseases of wheat. In recent years, the dominant position of leaf diseases of wheat is yellow leaf spot or pirenoforoza. Yellow blotch, caused by the fungus Drechslera tritici-repentis most widespread in many countries around the world, including Canada and the United States, as well as in the countries of Western Europe, Eastern and South and Central Asia. In recent years, there is a strengthening of yellow leaf spot severity in the southern, northern and south-eastern regions of Kazakhstan. Average yield losses are 15-20% and 40-60% epiphytoties conditions. Development of new varieties with disease resistance traits could significantly reduce the harmfulness threshold pathogen. The solution to this problem by traditional breeding continuously over time, since the evolution of the pathogen overtakes the possibility of obtaining breeders and sustainable forms of late with the introduction into production. To accelerate this problem we have used methods of biotechnology. The combination of conventional breeding methods with biotechnology allows for short term gain resistance to fungal disease forms of wheat. The studies examined phytotoxic and phytopathogenic fungus properties Drechslera tritici-repentis, selected strain Dtr 3/04 having high pathogenicity, phytotoxicity for use in cell selection of soft wheat for resistance to yellow spot.